A new species of terrestrial-breeding frog of the genus Pristimantis (Anura: Terrarana: Craugastoridae) from the eastern Andean slopes of the southern Ecuador - Valencia, Jorge H.; Valladares-Suntasig, Francisco; Tipantiza-Tuguminago, Luis; Dueñas, Manuel R. (Zootaxa, 2019)
A new frog of the genus Pristimantis is described from a montane cloud forest at 9 de Octubre (2°14’52” S, 78°16’37” W; 1778 m) province of Morona Santiago in the upper basin of the Upano River, southeastern Ecuador. The description of the new species is based on the examination of eleven adult males and three adult females. The new taxon can be readily distinguished from other congeneric species that inhabit the eastern Andes of Ecuador by the unique combination of the following characters: small body (adult males SVL 12.0–17.0 mm, adult females SVL 18.5–21.7 mm); skin of dorsum finely shagreen with two subconical scapular tubercles, weak and discontinuous dorsolateral folds in the middle of the back; large tympanum 70–93% of eye diameter; snout subacuminate in dorsal view, rounded in profile; upper eyelid bearing four or five small and flat supraocular tubercles; males lacking vocal slits and nuptial pads; all discs on fingers and toes lanceolate. Additionally, we provide information on the advertisement call and natural history of the new species.